2005
DOI: 10.1080/01480540500262961
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Glurenorm (Gliquidone) Treatment on the Liver Injury of Experimental Diabetes

Abstract: Oxidative stress plays an important role in chronic complications of diabetes mellitus, and hence the regulation of free radicals is essential in the treatment of diabetes. The aim of the current study is to investigate the effect of glurenorm (10 mg/kg) on liver tissue in experimental diabetes. Diabetes was induced by intraperitoneal injection of 65 mg/kg streptozotocin. Glurenorm was administered to one diabetic and one control group separately, from days 14 to 42. On day 42, cardiac blood samples and liver … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…Various means of preventing this increase have been investigated both in vitro and in vivo. It has been reported that various plant extracts [40,41], oral antidiabetic drugs [26], vitamin [42], and trace elements such as vanadium [43] and zinc [44] prevent the increase of tissue NEG levels [45]. In this study, the increase in NEG levels in liver tissue was considerably lowered by the combination of vitamin C, vitamin E, and Se.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Various means of preventing this increase have been investigated both in vitro and in vivo. It has been reported that various plant extracts [40,41], oral antidiabetic drugs [26], vitamin [42], and trace elements such as vanadium [43] and zinc [44] prevent the increase of tissue NEG levels [45]. In this study, the increase in NEG levels in liver tissue was considerably lowered by the combination of vitamin C, vitamin E, and Se.…”
Section: Discussionmentioning
confidence: 55%
“…During diabetes, we observed a significant decrease in GSH levels in liver tissue. In a similar manner, previous study have reported that there was a decreament in the liver GSH level of diabetic rats [26]. The decreased GSH levels represent increased utilization due to oxidative stress [27].…”
Section: Discussionmentioning
confidence: 77%
“…During the early onset of diabetes, oxidative stress occurs and progressively increases. Increased oxidative stress is believed to play a crucial role in the aetiology and pathogenesis of chronic complications of diabetes in diverse tissues . The link has been described between oxidative stress and the pathological alterations in liver morphology and function that are observed in diabetes .…”
Section: Mechanisms Involved In the Development Of Diabetic Liver Injurymentioning
confidence: 99%
“…Yarat et al [14] demonstrated that gliquidone markedly lowered the level of nonenzymatic glycosylation protein and total protein and increased the level of lens glutathione in diabetic rats. Yanardag et al [15] reported that gliquidone lessened the STZ-induced hepatic lesions by reducing oxidative stress in diabetic rats. In patients with diabetic nephropathy, substitution of oral glibenclamide with gliquidone has increased the glomerular filtration rate and lowered urinary albumin [16].…”
Section: Introductionmentioning
confidence: 99%